Bank Indonesia's Role in Maintaining Monetary Stability and the Payment System in Indonesia - M. Faisal Rahendra Lubis; Bella Br Tarigan; Siti Zahra Hsb; Hafizah Salsabilah Manik; Shafira Putri Azhari; Daffa A. Ananda Bayadi (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This article discusses the role of Bank Indonesia in maintaining monetary and payment system stability as an important part of national economic resilience. Monetary stability is understood as an effort to control inflation, maintain the value of the rupiah, and ensure that the amount of money in circulation is at a level appropriate for economic needs. The development of financial technology and the digitalization of payment systems have also influenced these stabilization mechanisms, requiring Bank Indonesia to adjust its policies to structural changes in the financial system. This research uses a normative legal method with a statute and conceptual approach, and is sourced from primary legal materials such as Article 23D of the 1945 Constitution, Law No. 23 of 1999, and Law no. 6 of 2009, as well as supported by secondary literature from books and scientific journals. The analysis results show that Bank Indonesia implements monetary stabilization through the BI-7DRR interest rate policy, open market operations, exchange rate intervention, and macroprudential instruments to maintain inflation and the stability of the rupiah's value. At the same time, BI's role in the payment system is realized through strengthening digital infrastructure such as QRIS and BI-FAST, improving cybersecurity, and regulations aimed at reducing systemic risk. Research findings also indicate that challenges in the digital age include cybercrime threats, infrastructure inequality, cryptocurrency developments, and the need for regulatory harmonization between institutions. Therefore, the future strategy requires BI to strengthen policy adaptation, increase digital financial literacy, and expand institutional synergies to ensure the sustained maintenance of monetary and payment system stability.